A comparative evaluation of three port versus standard four port laparoscopic cholecystectomy in SGRRIMHS and SMIH Dehradun - Singhal, Pradeep; Aggarwal, Amulya; Altamash, Syed; Verma, Ajay Kumar (International Surgery Journal, 2019)
Background: Cholelithiasis is one of most common condition requiring surgical intervention specially in females in Indo-Gangetic belt. Techniques of cholecystectomy have evolved from open to laparoscopic procedures. Efforts have been made to perform it with lesser ports for better operative outcomes like less complications and better cosmetic appearance. This study aims to compare the postoperative outcomes of 4 port versus 3 port laparoscopic cholecystectomy. Methods: This is a prospective comparative study. 104 patients for 4 port laparoscopic cholecystectomy and 110 patients for 3 port cholecystectomy were allocated randomly. Preoperative assessment was done in both the groups and Informed consent was taken. Intra operative parameters like duration of surgery, blood loss, surgical complications were assessed. Postoperative follow up was done at 1 week, and scar assessment at 2 weeks. Findings were entered in Microsoft Excel and analyzed using SPSS by applying t-test and chi-square test. Results: Female: male ratio was 14:1 and age varied between 32-51 years. The mean operative time was in 3 port was 64.6 min and 56.42 min in 4 port (p<0.05). Complications like conversion to open procedure, bleeding from liver bed, cystic artery bleeding and port site infections were comparable in both groups. Analgesic requirement was significantly less after 24 hours in 3 port (p=0.02). Conclusions: 3 ports cholecystectomy is better in terms of lesser postoperative pain, cosmetic outcome, hospital stay, lesser assistance. The authors recommend 3 ports LC as a routine procedure in gallstone diseases.